ANALYTICAL & CRITICAL STUDY OF DASTANBU’S URDU TRANSLATIONS - Dr. Ali Kavousi Nejad (Zaban-o-Adab, 2022)
Mirza Asaduallah Khan Ghalib is amongst the poets who were master in both Urdu and Persian prose and poetry. He was famed for his Persian prose & poetry throughout the Indian subcontinent. When Mughal dynasty was breathing its last, Ghalib was the only poet who strengthened Persian language and literature in those times of turmoil. In the mutiny of 1857 when British army captured the freedom fighters in Dehli, Ghalib recorded the accounts of fifteen months and wrote what he personally witnessed in Persian prose and the document was later named Dastanbu and became quite popular. Many scholars translated this book into Urdu. In this study we’ll be presenting analytical and critical review of these translations by referring to their strengths and limitations.